The Influence of Content Marketing on Generation Z Engagement on Instagram - Ogest Davina Natasya; Mutia Tri Satya (Pustaka Bangsa Indonesia, 2026)
This study analyzes the influence of content marketing on customer engagement on Instagram @posind_bandung among Generation Z students at Ekuitas University. The rapid growth of social media has encouraged companies to implement content marketing strategies; however, not all digital content successfully increases audience engagement. The method used in this study is a quantitative method with a descriptive and verification approach. A quantitative approach was employed using survey data collected from 100 respondents who follow Instagram @posind_bandung. Data were analyzed using simple linear regression, classical assumption tests, coefficient of determination (R-square), and t-test analysis. The results indicate that content marketing has a positive and significant effect on customer engagement. Content quality, clarity, and relevance contribute to increased interaction levels among followers. Conclusion: Effective content marketing strategies can enhance audience engagement and strengthen digital communication between organizations and audiences.